2017
DOI: 10.1145/3010078
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Challenges to Facilitate Situated Learning in Virtual Worlds Post-Second Life

Abstract: Virtual worlds can establish a stimulating environment to support a situated learning approach in which students simulate a task within a safe environment. While in previous years Second Life played a major role in providing such a virtual environment, there are now more and more alternative-often OpenSimbased-solutions deployed within the educational community. By drawing parallels to social networks, we discuss two aspects: how to link individually hosted virtual worlds together in order to implement context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In investigating virtual worlds as situated learning approaches, Conrad et al (2017) raised their concerns about the impact of "fake" accounts. By comparing to "profiling cloning" and fake accounts on social networking sites such as Facebook, they suggested that for activities such as education, the necessity for anonymity is no more justified and will make it difficult to trace back to the person that can be accountable when deliberate disturbances and negative intervenes occur.…”
Section: Threats To Accountabilitymentioning
confidence: 99%
“…In investigating virtual worlds as situated learning approaches, Conrad et al (2017) raised their concerns about the impact of "fake" accounts. By comparing to "profiling cloning" and fake accounts on social networking sites such as Facebook, they suggested that for activities such as education, the necessity for anonymity is no more justified and will make it difficult to trace back to the person that can be accountable when deliberate disturbances and negative intervenes occur.…”
Section: Threats To Accountabilitymentioning
confidence: 99%